Safeguarding youth health in climate-vulnerable countries - Aruta, John Jamir Benzon R; Guinto, Renzo R * (Elsevier, 2022)
The climate crisis is already causing serious consequences to many people’s lives around the world, with children and adolescents especially vulnerable to the physical and mental health eﬀects of the changing climate. An Editorial in The Lancet Child and Adolescent Health emphasised that the world is not on track to meet the global carbon net zero target by 2050. We concur with the recommendations for radical and urgent actions from world governments to preserve planetary and human health and to safeguard the health of children and adolescents in climate-vulnerable countries.